Quantifying how functional and structural personal factors influence biomechanical exposures in paramedic lifting tasks. - Armstrong, Daniel P.; Beach, Tyson A. C.; Fischer, Steven L. (Ergonomics, 2024)
It is unknown how structural (sex, stature, body mass) and functional (strength, flexibility) personal factors influence lifting strategy in paramedic work. We explored whether variance in peak low back forces and kinematic coordination patterns could be explained by structural and functional personal factors in paramedic lifting tasks. Seventy-two participants performed backboard and stretcher lifts. Peak low back forces normalised to body mass, as well as kinematic coordination patterns, were calculated as dependent variables. Being female, stronger, shorter, having higher body mass, and/or having greater lower body range of motion (ROM) were all independently associated with lower normalised low back forces across backboard and stretcher lifting. Females and stronger individuals seemed to define a movement objective to consistently minimise compressive forces, while individuals with greater hip ROM consistently minimised anteroposterior shear forces. The efficacy of improving strength and hip ROM to reduce low back forces in paramedic lifting should be investigated. Practitioner summary: Females, stronger individuals, and individuals with greater hip range of motion consistently exhibited lower normalised low back forces in paramedic lifting. Improving strength and hip range of motion via training is a potential proactive ergonomics approach to reduce peak low back forces in paramedic lifting tasks.